Reimagining Local Broadcasting Unveiling Dynamic Communication: Menata Ulang Penyiaran Lokal dengan Menghadirkan Komunikasi yang Dinamis - Indi Rachmawati; Kukuh Sinduwiatmo (Universitas Muhammadiyah Sidoarjo, 2024)
This qualitative study delves into the communication styles of broadcasters and listeners within the Lontong Balap RRI Surabaya program, aiming to fill gaps in understanding communication dynamics in local radio contexts. Data collection involved non-participant observation and interviews, with purposive sampling selecting informants from both broadcaster and listener demographics. Findings reveal a predominant equalitarian communication style, fostering direct interactions and natural engagement between broadcasters and listeners. The program serves to revive local culture while providing information and entertainment, showcasing the significance of relatable language and direct engagement in enhancing audience participation and program effectiveness within local radio broadcasts. Hghlight: Efficient Inventory System: PT. Perdana Sukses Makmur demonstrates effective inventory management practices. Internal Control Challenges: Addressing function combination enhances organizational oversight. Production Efficiency Implications: Refining internal controls enhances manufacturing performance. Keywoard: Inventory Management, Internal Control, Manufacturing Company, Qualitative Study, Indonesia